Combinatorial Biomatrix/Cell‐Based Therapies for Restoration of Host Tissue Architecture and Function. Issue 12 (5th July 2013) - Cantu, David Antonio; Kao, W. John
Abstract This Progress Report reviews recent advances in the utility of extracellular matrix (ECM)‐mimic biomaterials in presenting and delivering therapeutic cells to promote tissue healing. This overview gives a brief introduction of different cell types being used in regenerative medicine and tissue engineering while addressing critical issues that must be overcome before cell‐based approaches can be routinely employed in the clinic. A selection of five commonly used cell‐associated, biomaterial platforms (collagen, hyaluronic acid, fibrin, alginate, and poly(ethylene glycol)) are reviewed for treatment of a number of acute injury or diseases with emphasis on animal models and clinical trials. This article concludes with current challenges and future perspectives regarding foreign body host response to biomaterials and immunological reactions to allogeneic or xenogeneic cells, vascularization and angiogenesis, matching mechanical strength and anisotropy of native tissues, as well as other non‐technical issues regarding the clinical translation of biomatrix/cell‐based therapies.